20 points! Thanks for the help :)
![20 points Thanks for the help class=](https://us-static.z-dn.net/files/ddc/51fd64bbdbb36c7d74db3676f04d5581.jpg)
Answer:
Step-by-step explanation:
a) (-2x³ + x - 5)(x³ - 3x - 4)
= (-2x³) (x³ - 3x - 4) + x(x³ - 3x - 4) - 5(x³ - 3x - 4)
= -2x³*x³ - (-2x³)*3x - (-2x³)*4 + x*x³ - x*3x - x*4 + x³ * (-5) - 3x*(-5) -4*(-5)
= -2x⁶ + 6x⁴ + 8x³ + x⁴ - 3x² -4x - 5x³ + 15x + 20 {add like terms}
= -2x⁶ + 6x⁴ + x⁴ + 8x³ - 5x³ - 3x² - 4x + 15x + 20
= -2x⁶ + 7x⁴ + 3x³ - 3x² + 11x + 20
Hint: When multiplying two terms, multiply the coefficient, and add the powers of the variables {[tex]a^{m}*a^{n}=a^{m+n}[/tex] }
-2x³*x³ = (-2*1) * [tex]x^{3+3}[/tex] = -2x⁶
b) Yes , same because of commutative property of multiplication
Answer:
[tex]-2x^6+7x^4+3x^3-3x^2+11x+20[/tex]
Step-by-step explanation:
a) We can expand [tex](-2x^3 + x - 5) (x^3 - 3x - 4)[/tex], getting [tex]-2x^6+6x^4+8x^3+x^4-3x^2-4x-5x^3+15x+20[/tex]. We can then combine like terms, getting [tex]-2x^6+7x^4+3x^3-3x^2+11x+20[/tex].
b) Yes it is the same, as it doesn't matter the order if you multiply two polynomials. It will always be the same.